Efficacy of a mindful-eating programme to reduce emotional eating in patients suffering from overweight or obesity in primary care settings: a cluster-randomised trial protocol - Morillo Sarto, Hector (BMJ Open, 2019)
INTRODUCTION: Little is known about the applicability of mindfulness-based interventions in Spanish adults with overweight/obesity. The objective of the present study protocol is to describe the methods that will be used in a cluster randomised trial (CRT) that aims to evaluate the effectiveness of a mindfulness eating (ME) programme to reduce emotional eating (EE) in adults with overweight/obesity in primary care (PC) settings. METHODS AND ANALYSIS: A CRT will be conducted with approximately 76 adults with overweight/obesity from four PC health centres (clusters) in the city of Zaragoza, Spain. Health centres matched to the average per capita income of the assigned population will be randomly allocated into two groups: ‘ME +treatment as usual (TAU)’ and ‘TAU alone’. The ME programme will be composed of seven sessions delivered by a clinical psychologist, and TAU will be offered by general practitioners. The primary outcome will be EE measured by the Dutch Eating Behaviour Questionnaire (DEBQ) at post test as primary endpoint. Other outcomes will be external and restrained eating (DEBQ), binge eating (Bulimic Investigatory Test Edinburgh), eating disorder (Eating Attitude Test), anxiety (General Anxiety Disorder-7), depression (Patient Health Questionnaire-9), mindful eating (Mindful Eating Scale), dispositional mindfulness (Five Facet Mindfulness Questionnaire) and self-compassion (Self-Compassion Scale). Anthropometric measures, vital signs and blood tests will be taken. A primary intention-to-treat analysis on EE will be conducted using linear mixed models. Supplementary analyses will include secondary outcomes and 1-year follow-up measures; adjusted models controlling for sex, weight status and levels of anxiety and depression; the complier average causal effect of treatment; and the clinical significance of improvements. ETHICS AND DISSEMINATION: Positive results of this study may have a significant impact on one of the most important current health-related problems. Approval was obtained from the Ethics Committee of the Regional Authority. The results will be submitted to peer-reviewed journals, and reports will be sent to participants. TRIAL REGISTRATION NUMBER: NCT03927534 (5/2019).